Life of Pi [a novel] - Martel, Yann. (Minneapolis, MN : HighBridge, 2002)
"After the tragic sinking of a cargo ship in the Pacific, one solitary lifeboat remains, carrying a hyena, a zebra, a female orangutan, a Bengal tiger, and a 16-year-old Indian boy names Pi. His story is a dazzling work of imagination that will delight and astound listeners in equal measure. It is a triumph of storytelling and a tale that will as one character puts it, make you believe in God"--Container.
Read by Jeff Woodman with Alexander Marshall.
Keywords: Human-animal relationships -- Fiction; Ocean travel -- Fiction; Orphans -- Fiction; Storytelling -- Fiction; Shipwreck survival -- Fiction; Teenage boys -- Fiction; Tiger -- Fiction; Zoo animals -- Fiction; Pacific Ocean -- Fiction; Psychological fiction; Adventure fiction